Muzakki's Determination In Paying Professional Zakat Through BAZNAS With Attitude As A Mediation Variable - Wahyu Angko Saputro; Nirdukita Ratnawati; Soeharjoto Soeharjoto (UNIVED Press, 2025)
This research was conducted to analyze muzakki's determination in paying professional zakat through the National Zakat Amil Agency (BAZNAS). The variables used refer to the Theory of Planned Behavior including Subjective Norm, Perceived Behavioral Control and Attitude then added with external variables namely Digitalization of Zakat which is one of the strategies to increase zakat receipts from BAZNAS and Religiosity where the Attitude variable is a mediating variable. The case study was conducted on professional zakat payments in DKI Jakarta Province. The study was conducted on employees from various institutions in the DKI Jakarta area using purposive sampling and obtained a total of 151 respondents. The data analysis technique uses the SEM-PLS method which aims to see the relationship between variables. Based on the results of the analysis using the SEM-PLS method, the first result was that digitalization of zakat and religiosity had a significant and positive effect on muzakki's intention to pay zakat income, while subjective norms and perceived behavioral control had no effect. Second, subjective norms, digitalization of zakat, and religiosity have a significant and positive effect on attitude, while perceived behavioral control has no effect. Third, attitude mediates the influence of subjective norms, digitalization of zakat, and religiosity on muzakki's intention to pay zakat on income, while regarding perceived behavioral control, attitude does not play a mediating role. This shows that attitude is one of the most important factors for individuals in paying zakat through BAZNAS.